2016
DOI: 10.1108/ejim-08-2014-0092
|View full text |Cite
|
Sign up to set email alerts
|

The combined effect of technological relatedness and knowledge utilization on explorative and exploitative invention performance post-M & A

Abstract: Purpose – The purpose of this paper is to investigate the combined effect of Mergers and Acquisitions (M & A) partners’ technological relatedness and the acquirer’s effective utilization of the target’s knowledge on explorative and exploitative invention performance post-M & A. Design/methodology/approach – Based on the knowledge perspective of an M & A, this study measures how much of the target’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 75 publications
1
47
1
2
Order By: Relevance
“…Knowledge must be used as the basis for the development of new knowledge through integration, innovation, creation, and extension of the existing knowledge basis, and should still be used as a basis for decision making. Thus, the use has an exploitative character of knowledge when through it decision or improvements are made, using, therefore, the same knowledge basis; or an explorative character, when the knowledge basis is used as a primary knowledge to create new knowledge in an innovative proposal (Cohen & Levinthal, 1990;Ganzaroli et al, 2016;Nooteboom et al, 2007).…”
Section: Knowledge Usementioning
confidence: 99%
See 2 more Smart Citations
“…Knowledge must be used as the basis for the development of new knowledge through integration, innovation, creation, and extension of the existing knowledge basis, and should still be used as a basis for decision making. Thus, the use has an exploitative character of knowledge when through it decision or improvements are made, using, therefore, the same knowledge basis; or an explorative character, when the knowledge basis is used as a primary knowledge to create new knowledge in an innovative proposal (Cohen & Levinthal, 1990;Ganzaroli et al, 2016;Nooteboom et al, 2007).…”
Section: Knowledge Usementioning
confidence: 99%
“…At this stage, interest is focused on forms of location and access to knowledge created and stored. It is through the use of retained knowledge that the organization closes the cycle of knowledge transformation, since knowledge was created under certain conditions, stored and distributed among individuals and, at this point, used for another purpose, promoting its transformation and the creation of new knowledge (Ganzaroli et al, 2016). The first topic addressed in publications refers to the form of use, i.e., if the organization exploited acquired knowledge in a reactive manner, usually related to solving problems presented by processes; or considers an exploitative view of knowledge in which the organization innovates from the consolidated knowledge basis (Cohen & Levinthal, 1990).…”
Section: Knowledge Retrieval and Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, companies that exploit new knowledge generate great variation in performance, while the use of exploitation leads to a more stable performance. Levinthal & March (1993) and Ganzaroli et al (2016) argue that it is important for companies to maintain an appropriate balance between exploration and exploitation to increase competitiveness. Holmqvist (2004) found that exploration and exploitation require significantly different structures, processes, strategies, capacity, and culture.…”
Section: Innovation Based On Knowledge Exploration and Exploitationmentioning
confidence: 99%
“…According to Levinthal & March (1993), Ganzaroli et al (2016) and Gupta et al (2006), organizations must balance their exploration and exploitation strategies. The authors argue that an excessive focus on exploitation results in organizational "short-sightedness," hindering innovation and leading to a process of obsolescence.…”
Section: Innovation Based On Knowledge Exploration and Exploitationmentioning
confidence: 99%